Comparing standards of business ethics in USA, China, Jamaica and Pakistan - Abdul Ghani Tabis (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
As the business organizations are expanding at a rapid pace, so is the circulation of human resources the world over. Managers and workers are required to work in different socio-economic environments which, at times, may not be similar to those of their home countries. It is imperative therefore for business organizations and individuals to acquire in depth knowledge about the culture and business ethics prevailing in the country of interest. A number of scholars have undertaken research studies to compare the standards of Business Ethics of different countries but such a research on "the Standards of Business Ethics" has been carried out for the first time in Pakistan. Interestingly, either such studies have been carried out in developed countries like Europe, America and Far East or the researchers have been from these countries. The conduct of such a study in Pakistan by a Pakistani would be the first of its nature. Some of the internationally accepted norms have been used as scenarios and respondents have been asked to indicate possibility of their reaction to take action. They have also been asked to give rationale of their decision. An effort has been made in this study, to compare the standards of business ethics of Pakistani business professionals with those of other countries of the world. This would help adjudge differences and similarities of well-established universal norms and ethics prevailing in the world business community. It is expected that this and more such studies would help researchers and business professionals develop good and desirable business practices in Pakistan.Comparing and enhancing awareness about standards of business ethics in Pakistan is the main objective of this research. It is expected that this humble effort would encourage many more researchers to dive deep into the ocean of business ethics.
Keywords: 330; Business Ethics; Ethical Standards; Social Ethics; Morality in Business; Business Norms